Kepemimpinan dan Organisasi dalam Optimalisasi Sumber Daya Manusia - Iman Rozikin Bayu Aji; M. A. Hermawan (Reslaj: Religion Education Social Laa Roiba Journal, 2026)
This study aims to analyze the role of leadership and organizational culture in optimizing human resources (HR), particularly within the educational sector. The research employs a qualitative method using a literature review approach by analyzing various sources related to leadership, organization, and human resource management. The findings reveal that leadership has a significant impact on improving HR quality. Effective school leaders can foster a positive, participative, and collaborative organizational culture that motivates teachers to enhance their performance and professionalism. Furthermore, a strong organizational culture plays an essential role in creating a conducive work environment, increasing productivity, and strengthening members’ commitment. In conclusion, the synergy between effective leadership and a positive organizational culture is a key factor in optimizing HR to achieve sustainable educational goals.